2022
DOI: 10.1021/acsearthspacechem.2c00043
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Organosulfate-Dominated Aerosols over Agricultural Fields from the Southern Great Plains by High-Resolution Mass Spectrometry

Abstract: The molecular composition of organic aerosols, especially for day/nighttime variations of organosulfates above agricultural fields, is not well understood despite profound impacts on regional climate, crop production, air quality, and human health. Here, nanospray desorption electrospray ionization with high-resolution mass spectrometry (nano-DESI-HRMS) is used to interrogate the molecular composition of organic aerosols collected at the Southern Great Plains, located in an agricultural region of Oklahoma. Ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 65 publications
4
14
0
Order By: Relevance
“…The increasing abundance of sulfuric acid with back trajectories from the south is consistent with the results of Hodshire et al (2016) who demonstrated that sulfuric acid contributes significantly to SGP particle growth when air masses originate from the south. It is also broadly consistent with the recent work of Vandergrift et al (2022) which showed that many organosulfates in SOA were unique to air masses originating from the south. The increase in the low m/z nitrates factor in the southeast cluster could result from increased biogenic emissions to the east of the site.…”
Section: Negative Factor Back Trajectory Clusterssupporting
confidence: 91%
See 2 more Smart Citations
“…The increasing abundance of sulfuric acid with back trajectories from the south is consistent with the results of Hodshire et al (2016) who demonstrated that sulfuric acid contributes significantly to SGP particle growth when air masses originate from the south. It is also broadly consistent with the recent work of Vandergrift et al (2022) which showed that many organosulfates in SOA were unique to air masses originating from the south. The increase in the low m/z nitrates factor in the southeast cluster could result from increased biogenic emissions to the east of the site.…”
Section: Negative Factor Back Trajectory Clusterssupporting
confidence: 91%
“…Glycolic acid sulfate has been previously observed in the gas-phase (Ehn et al, 2010;Le Breton et al, 2018). In addition to gas-phase measurements, glycolic acid sulfate has been detected in SOA derived from isoprene and its oxidation products in both ambient samples (Surratt et al, 2008;Safi Shalamzari et al, 2013;Wach et al, 2019;Vandergrift et al, 2022) and chamber experiments (Surratt et al, 2008;Galloway et al, 2009;Wach et al, 2019).…”
Section: Organosulfatesmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar strategies to those used here for data analysis, including blank subtraction and data filtering, have been previously described. 46 Molecular formulae assignment was conducted using MFAssignR, 47 an open source software tool. Assigned molecular formula were limited to C, H, N (maximum of 2 per individual formula) and O elemental constituents of deprotonated, singly-charged ion types.…”
Section: Methodsmentioning
confidence: 99%
“…C, H, and S (maximum of 1) atoms were allowed in both ion modes. A detailed description of the nano-DESI-HRMS methodology used herein has been previously described 71 and is provided in the Supporting Information Section S2.…”
Section: Soa Growth Experimentsmentioning
confidence: 99%